ANALISIS FAKTOR YANG MEMPENGARUHI MINAT BELI KOLEKSI KEBAYA MEGA ARUM COLLECTION KLATEN - Apriliyani, Vika; Susanti, Ari (Jurnal Akuntansi dan Bisnis, 2023)
This research was conducted with the aim of examining the effect of Perceived Quality (X1), Brand Trust (X2) and Word of Mouth (X3) on Purchase Intention (Y) of the Mega Arum Collection kebaya collection. This type of research is a quantitative method. Using the Roscoe technique and purposive sampling, the number of respondents in this study was 100 samples who were old and new consumers of Mega Arum Collection. The population in this study were consumers of the Mega Arum collection in the Klaten area and the sample criteria in this study were consumers who had purchased the Mega Arum collection. This study uses multiple linear regression analysis techniques. The research results obtained, Perceived Quality (X1) has no effect on Purchase Intention (Y), while Brand Trust (X2) has an effect on Purchase Intention (Y), then Word of Mouth (X3) has no effect on Purchase Intention. Keywords: Perceived Quality, Brand Trust, Word of Mouth.